Water, Sanitation, Waste Management, and Professional Activities in Relation to Diseases with Neighboring Citizens of Congo Rivers in the Brazzaville Agglomeration (Republic of Congo) - Orline Lesley Mbianda Nfong-Ya; Jean De Dieu Nzila; Raison Félicien Louzayadio Mvouezolo; Longin Justin Clair Bonazaba Milandou; Isidore Nguelet-Moukaha; Georgy Patience Wando; Jean Maurille Ouamba; Martin Pépin Aina (European Scientific Journal, ESJ, 2024)
Situated on the right bank of the Pool Malébo, in the Congo River basin, the city of Brazzaville is rich in potential water resources. These resources are polluted by human practices that deteriorate the quality of the soil and, consequently, the quality of the water. The aim of this study is therefore to inventory the activities carried out by the population around watercourses, to investigate waste management and to assess the impact on water and soil quality. The survey sample was selected on the basis of impacted zones located between 250 m and 750 m around watercourses. The aim of this study is therefore to inventory the activities carried out by the population around watercourses, to investigate waste management and to assess the impact on water and soil quality. The survey form was drawn up using Sphinx Plus2-Edition Lexica-V5 software. The survey data was entered into the same software, then transferred to Excel to generate the graphical. 880 people were surveyed, the most dominant age group was 25-48 years old, i.e. a rate of 66%. The most dominant gender was female, with a rate of 54%. The average age of the respondents was lower secondary school, and they were generally employed in the private sector. Commercial activities (restaurants/bars, pharmacies, grocery stores/ butchers, markets, etc.) are the most common economic activity, with a rate of around 70%; 59% of these activities are located close to or very close to the watercourse (750-1000 m). The activities that contribute to soil degradation, and consequently water degradation, in the city of Brazzaville are: 59% the dumping of household waste and/or wastewater on the ground and 32% uncontrolled urbanization. The study shows that soil and water pollution in Brazzaville is caused by poor management of household waste and uncontrolled urbanization.